Peningkatan Prestasi Belajar Materi Logaritma melalui Pemahaman Konsep dalam Pembelajaran Matematika pada Siswa Kelas X TKJ1 SMK Negeri 1 Sawit Kabupaten Boyolali Semester Gasal Tahun Pelajaran 2011/2012 - Sutanto, Sutanto (Jurnal Varidika: Varia Pendidikan, 2015)
The research was inspired by the unsatisfactory attainment of students on understanding concept implementation (learning mastery) through logaritm at class X students TKJI SMK Negeri Sawit Boyolali Regency odd semester 2011/2012. The research aim at describing the optimalisation of logarithm subject mastery. The subject and data source of the research are 39 students of class X TKJI SMK Negeri Sawit Boyolali Regency by using obseravtion documentation and test. The data analysis uses critical and comparative data analysis. The completion indicator used is 69. The research uses a cycle procedure. The findingsÂ  from cycle I, II and II show that there is a progress motivation of the students in the class. In Cycle I 67 average, cycle II 83 and cycle III 92. This shows the significant increase on the motivation of the students from cycle I until cycle III